Climate transition risk stress test for the German financial system - Ivan Frankovic; Tobias Etzel; Alexander Falter; Christian Gross; Jana Ohls; Lena Strobel; Hannes Wilke (Deutsche Bundesbank, 2023)
This paper presents the methodology applied in the Deutsche Bundesbank's climate transition stress test for the German financial system, see Deutsche Bundesbank (2023). It discusses the construction of the transition scenarios underlying the analysis, including a long-run orderly scenario and a more disruptive short-term carbon price shock. Furthermore, the document shows the methodology for translating scenario impacts onto the asset level, which includes the consideration of firm-level carbon emission data where available. Finally, the impacts on the balance sheets of German banks, funds and insurers are discussed.
Keywords: G2; H23; Q5; 330; climate risks; stress testing; climate scenarios; financial stability